2013
DOI: 10.1002/jhm.2016
|View full text |Cite
|
Sign up to set email alerts
|

How do attendings perceive housestaff autonomy? Attending experience, hospitalists, and trends over time

Abstract: BACKGROUND: Graduated supervision is necessary for residents to progress to independence, but it is unclear what factors influence attendings' perception of housestaff autonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…A number of models have been published suggesting that supervision can be enhanced without severely compromising trainee autonomy [9, 19, 25, 26]. While the authors believe that this study reasonably measures important of aspects of supervision in the outpatient clinic setting, they concede that autonomy is a perception [14, 27, 28] and may be much more difficult to measure. However, the significant body of published literature describing the tension between autonomy and supervision suggest that they most likely vary inversely [15, 29–32].…”
Section: Discussionmentioning
confidence: 91%
“…A number of models have been published suggesting that supervision can be enhanced without severely compromising trainee autonomy [9, 19, 25, 26]. While the authors believe that this study reasonably measures important of aspects of supervision in the outpatient clinic setting, they concede that autonomy is a perception [14, 27, 28] and may be much more difficult to measure. However, the significant body of published literature describing the tension between autonomy and supervision suggest that they most likely vary inversely [15, 29–32].…”
Section: Discussionmentioning
confidence: 91%
“…[1][2][3] Recent studies have suggested that provision of autonomy is an area of concern for faculty and residents. 4,5 Trainees express that they are not given enough opportunities to participate in clinical decision making, while faculty identify the challenges of supporting autonomy for residents in settings of high acuity, high patient census, and limited trainee experience. 6 Family-centered rounds (FCR), defined as interdisciplinary bedside rounds where the ''patient and family share in the control of the management plans,'' 7 have become a widely adopted model for rounds in the pediatric setting.…”
Section: Introductionmentioning
confidence: 99%
“…5,7,13,14,33 Of 118 total residents, we e-mailed invitations to 30 using random purposive sampling based on training year. We invited PGY2 and PGY3 IM residents at UCSF for interviews.…”
Section: Phase 1: Interviews and Focus Groupsmentioning
confidence: 99%
“…[1][2][3][4][5][6] Trust relates to both the person doing the trusting (supervising physician) and the person who is trusted (trainee) and can entail a belief, decision, and action. [1][2][3][4][5][6] Trust relates to both the person doing the trusting (supervising physician) and the person who is trusted (trainee) and can entail a belief, decision, and action.…”
mentioning
confidence: 99%
See 1 more Smart Citation